Thermal fluctuations of director orientation in nematic liquid crystals with inclusions - Vasil’ev, A.N.; Pinkevich, I.P. (Condensed Matter Physics, 2005)
We investigate thermal fluctuations of order parameters (director for mesomorphic
subsystem and density for isomorphic liquid) in filled liquid crystal.
We consider finite-size system with geometry of plane-parallel layer with
zero boundary condition. We use a special model that takes into account
the interaction of mesomorphic and isotropic subsystems and find general
expressions for pair correlators. Based on these expressions we calculate
the shift of critical temperature of isotropic liquid due to the interaction with
the mesomorphic subsystem and space limitation. Досліджуються теплові флуктуації параметрів порядку (директор
для рідкокристалічної підсистеми та густина для ізотропної рідини)
в рідкому кристалі з домішками. Розглядається просторово обмежена система з геометрією плоского паралельного прошарку з нульовими граничними умовами. Запропоновано модель, що враховує
взаємодію рідкокристалічної та ізотропної підсистем та знаходяться загальні вирази для парних кореляторів. На основі цих виразів
розраховується зсув критичної температури ізотропної підсистеми,
що виникає внаслідок взаємодії з рідким кристалом та через просторове обмеження.